Optimal sunscreen use, during a sun holiday with a very high ultraviolet index, allows vitamin D synthesis without sunburn. (1st November 2019) - Young, A.R.; Narbutt, J.; Harrison, G.I.; Lawrence, K.P.; Bell, M.; O'Connor, C.; Olsen, P.; Grys, K.; Baczynska, K.A.; Rogowski‐Tylman, M.; Wulf, H.C.; Lesiak, A.; et al.
Summary: Background: Sunlight contains ultraviolet (UV)A and UVB radiation. UVB is essential for vitamin D synthesis but is the main cause of sunburn and skin cancer. Sunscreen use is advocated to reduce the sun's adverse effects but may compromise vitamin D status. Objectives: To assess the ability of two intervention sunscreens to inhibit vitamin D synthesis during a week‐long sun holiday. Methods: The impact of sunscreens on vitamin D status was studied during a 1‐week sun holiday in Tenerife (28° N). Comparisons were made between two formulations, each with a sun protection factor (SPF) of 15. The UVA‐protection factor (PF) was low in one case and high in the other. Healthy Polish volunteers ( n = 20 per group) were given the sunscreens and advised on the correct application. Comparisons were also made with discretionary sunscreen use ( n = 22) and nonholiday groups (51·8° N, n = 17). Sunscreen use in the intervention groups was measured. Behaviour, UV radiation exposure, clothing cover and sunburn were monitored. Serum 25‐hydroxyvitamin D3 [25(OH)D3 ] was assessed by high‐performance liquid chromatography–tandem mass spectrometry. Results: Use of intervention sunscreens was the same ( P = 0·60), and both equally inhibited sunburn, which was present in the discretionary use group. There was an increase ( P < 0·001) in mean ± SD 25(OH)D3 (28·0 ± 16·5 nmol L −1 ) in the discretionary use group. The high and low UVA‐PF sunscreen groups showed statistically significant increases ( P < 0·001) of 19·0 ± 14·2 and 13·0 ± 11·4 nmol L −1 25(OH)D3, respectively with P = 0·022 for difference between the intervention sunscreens. The nonholiday group showed a fall ( P = 0·08) of 2·5 ± 5·6 nmol L −1 25(OH)D3 . Conclusions: Sunscreens may be used to prevent sunburn yet allow vitamin D synthesis. A high UVA‐PF sunscreen enables significantly higher vitamin D synthesis than a low UVA‐PF sunscreen because the former, by default, transmits more UVB than the latter. What's already known about this topic? Action spectra (wavelength dependence) for erythema and the cutaneous formation of vitamin D overlap considerably in the ultraviolet (UV)B region. Theoretically, sunscreens that inhibit erythema should also inhibit vitamin D synthesis. To date, studies on the inhibitory effects of sunscreens on vitamin D synthesis have given conflicting results, possibly, in part, because people typically apply sunscreen suboptimally. Many studies have design flaws. What does this study add? Sunscreens (sun protection factor, SPF 15) applied at sufficient thickness to inhibit sunburn during a week‐long holiday with a very high UV index still allow a highly significant improvement of serum 25‐hydroxyvitamin D3 concentration. An SPF 15 formulation with high UVA protection enables better vitamin D synthesis than a low UVA protection product. The former allows more UVB transmission.